SUMBER BELAJAR EKOLOGI: FEKUITIDITAS IKAN SERIBU (LEBISTES RETICULATUS PETERS.) DI PERAIRAN SUNGAI GAJAH WONG, YOGYAKARTA - Nurusman, Arief Abdillah (BIOEDUKASI, 2006)
AbstractThis research was aimed to know the inflaence of water quality and pollution on fecundity of l*bistesreticulatus Peters. The result of this research will show how environmental factors act toward the organism onseveral levels of ecological hierarchy. The disscussion of it then will enrich student's understanding about theeffect of environmental fastors toward the organism. That is the material to learn,This research was carried out upon Gajah Wong river precisely on water mass which polluted bytannery waste and the water mass out of polluted area. Three sampling were carried out along the trasect whichcover the befor- polluted area, the outlet of waste and the water mass polluted by the waste. Embrio was thencounted for measure the fecundity.The result shows that pollution affect the fecundity of Lebistes reticalqtus by turning the fecunditylower. Pollution caused the change of dissolved orygen and water acidity from its normal condition. Indeed,pollution caused the low environmental quality, even for reproduction of the more-tolerannt fish. Disscussionupon that result will enrich student's understanding about the ffict of pollution toward living thing. Bycarrying the student into the field during teaching and learning proccesses and practicing on ecology, theunderstanding will go into effectively.Key words: Lebistes reticulatus'fecundity, tannery pollution, teaching materials